Analysis and Implementation of Performance Metrics, Parameters and Factors of Ad Hoc, Cloud and Ad Hoc Cloud Network - Lakshmi Singh, Vijaya; Rai, Dinesh (International Journal of Engineering and Technology, 2019)
Ad hoc network is a network which is decentralized in nature that organizes its network, transmission and delivery of message is executed by nodes themselves. The concept of cloud is getting popular because of the idea of the use of the online information, software and hardware. The utilization of these non-dedicated infrastructures can be increased using a framework known as Ad hoc cloud. Popularity of these networks makes its performance evaluation is of vital importance. This paper is twofold, study is done to identify the most effective performance metrics, factors and parameters that effect the performance evaluation of these networks and then Ad-hoc On-demand Distance Vector (AODV) routing protocol is implemented and analyzed using OPNET Modeler.Â Â Â